Commodity Hoarding by Farmers in West Lombok through the Lens of Maqaṣid al-Shariʿah: A Socio-Legal Analysis - Samsul Karmaen (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Food commodity storage by farmers remains a critical issue in Islamic economic ethics, particularly when legitimate survival strategies intersect with the risk of market distortion and public harm. This study examines food commodity storage and hoarding practices among farmers in West Lombok Regency, Indonesia, through the perspectives of Islamic jurisprudence (fiqh muʿāmalāt) and Maqāṣid al-Sharīʿah. Employing a qualitative socio-legal research design, the study integrates normative Islamic legal analysis with the socio-economic realities of smallholder farmers operating within imperfect market structures. Data were obtained through a systematic literature review, doctrinal legal analysis, and contextual examination of local food market dynamics. The findings indicate that farmers’ storage practices are jurisprudentially permissible when motivated by legitimate economic survival needs and when they do not cause material harm (maḍarrat) to the wider public. However, such practices become prohibited as iḥtikār when conducted in an organized manner that creates artificial scarcity and triggers price increases detrimental to consumers. The Maqāṣid al-Sharīʿah framework, particularly the protection of life (ḥifẓ al-nafs), wealth (ḥifẓ al-māl), and public interest (al-maṣlaḥah al-ʿāmmah), provides a context-sensitive analytical lens that moves beyond rigid doctrinal prohibition while recognizing the structural vulnerabilities of peasant economies. This study contributes to Islamic socio-legal scholarship by demonstrating the relevance of Maqāṣid al-Sharīʿah in evaluating commodity storage practices and offers practical implications for integrating Islamic legal-ethical values into national food policy to support a just, sustainable, and welfare-oriented food system.